Deamidation of Cdc42 and Rac by Escherichia coli Cytotoxic Necrotizing Factor 1: Activation of c-Jun N-Terminal Kinase in HeLa Cells - Lerm, M. (American Society for Microbiology, 1999)
Recently, Escherichia coli cytotoxic necrotizing factor 1 (CNF1) was shown to activate the low-molecular-mass GTPase RhoA by deamidation of Gln63, thereby inhibiting intrinsic and GTPase-activating protein (GAP)-stimulated GTPase activities (G. Schmidt, P. Sehr, M. Wilm, J. Selzer, M. Mann, and K. Aktories, Nature 387:725–729, 1997; G. Flatau, E. Lemichez, M. Gauthier, P. Chardin, S. Paris, C. Fiorentini, and P. Boquet, Nature 387:729–733, 1997). Here we report that in addition to RhoA, Cdc42 and Rac also are targets for CNF1 in vitro and in intact cells. Treatment of HeLa cells with CNF1 induced a transient formation of microspikes and formation of membrane ruffles. CNF1 caused a transient 10- to 50-fold increase in the activity of the c-Jun N-terminal kinase. Tryptic peptides of Cdc42 obtained from CNF1-treated cells by immunoprecipitation exhibited an increase in mass of 1 Da compared to control peptides, indicating the deamidation of glutamine 61 by the toxin. The same increase in mass was observed with the respective peptides obtained from CNF1-modified recombinant Cdc42 and Rac1. Modification of recombinant Cdc42 and Rac1 by CNF1 inhibited intrinsic and GAP-stimulated GTPase activities and retarded binding of 2′(3′)-O-(N-methylanthraniloyl)GDP. The data suggest that recombinant as well as cellular Cdc42 and Rac are substrates for CNF1.